Optimizing of tray arrangement for the production of hydroponic green fodder from Avena sativa - Rodriguez, Wilson Andrés Mautone; Escudero, Anibal Alejandro Carrossio; Padron, Richard Alberto Rodriguez (Revista de Ciências Agroveterinárias, 2025)
Hydroponic green forage is an alternative from the point of view of nutritional supplement and it is estimated that the water savings in these systems can be significant, saving up to 90% compared to conventional irrigation methods. The objective of this research was to evaluate the arrangement of the trays in a hydroponic green forage production system with water recirculation, to determine the effect on the performance of the oat crop. The test consisted of 80 polyethylene trays; each tray has an area of 0.167 m2. In the evaluated treatments, the water flow was configured in two distinct ways. Nutrient solution (18-18-18) was applied, applying 90 grams in 150 liters of water. In Treatment A, the flow pattern alternates between levels in a zigzag manner: at levels 4 and 2, water flows from the center to the sides, whereas at levels 3 and 1, it flows from the sides to the center, where the excess volume is collected. In Treatment B, the water flow is more uniform: at levels 4, 3, and 2, it is directed from the center to the sides, ensuring an orderly descent, while at level 1, it is channeled from the sides to the center towards the collection point. This configuration simplifies system management and facilitates efficient water drainage. To compare the treatments, the following variables were evaluated: plant height and total dry matter. The arrangement of the tray with water recirculation showed a significant effect on the dry matter yield in the oat crop. The arrangements that favor better performance and greater production of dry matter were the trays with the arrangement towards the outside of the rack.